INVENTARISASI GULMA DI KEBUN BAH BIRUNG ULU PT. PERKEBUNAN NUSANTARA IV REGIONAL II: WEED INVENTORY IN BAH BIRUNG ULU GARDEN PT. PERKEBUNAN NUSANTARA IV REGION II - Nurliana; Irham, Wardatul Husna; Latif, Abdul (Agro Estate, 2025)
Weeds are nuisance plants that compete with the main crop, namely oil palm plants, in absorbing nutrients. If not controlled, the presence of weeds can cause a decrease in oil palm plant productivity. Inventory of dominant weeds in the highlands facilitates weed control at an altitude of 600-1000 meters above sea level (MDPL). The study was conducted at PT. Perkebunan Nusantara IV Kebun Bah Birung Ulu in Afdeling I, the research time started in February to March 2025. This study used a quantitative descriptive method with a direct weed identification method. The weed identification study in the highlands was at an altitude of 950 masl. The parameters observed were weed grouping, obtaining the Summed Dominance Ratio and the Important Value Index. From the results of the observations, it can be concluded that there are 12 types of weeds with the highest INP of 87%, namely Murdannia Nudiflora. The Summed Dominance Ratio analysis shows that Murdannia nudiflora has the highest dominance, while Spermacoce Ocymifolia has the lowest dominance.